2003
DOI: 10.1128/iai.71.7.3690-3698.2003
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Small-Colony Variants of Salmonella enterica Serovar Typhimurium in Nonphagocytic Eucaryotic Cells

Abstract: Salmonella enterica strains are enteropathogenic bacteria that survive and proliferate within vacuolar compartments of epithelial and phagocytic cells. Recently, it has been reported that fibroblast cells are capable of restricting S. enterica serovar Typhimurium intracellular growth. Here, we show that prolonged residence of bacteria in the intracellular environment of fibroblasts results in the appearance of genetically stable smallcolony variants (SCV). A total of 103 SCV isolates, obtained from four indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 61 publications
2
62
0
Order By: Relevance
“…This shows that environmental adaptation through PerR is essential for complete virulence in L. monocytogenes and that the true phenotype may be underrepresented in clones that have developed a secondary mutation (⌬perR lg ). It is likely that the ⌬perR sm mutant examined in this study differs from the general small-colony variants that have been isolated from infections caused by a variety of gramnegative and gram-positive organisms (9,44,45,48,49). These small-colony variants actually have a greater capacity to persist intracellularly than the wild type, whereas the ⌬perR sm mutant has a greatly reduced virulence potential.…”
Section: Discussionmentioning
confidence: 67%
“…This shows that environmental adaptation through PerR is essential for complete virulence in L. monocytogenes and that the true phenotype may be underrepresented in clones that have developed a secondary mutation (⌬perR lg ). It is likely that the ⌬perR sm mutant examined in this study differs from the general small-colony variants that have been isolated from infections caused by a variety of gramnegative and gram-positive organisms (9,44,45,48,49). These small-colony variants actually have a greater capacity to persist intracellularly than the wild type, whereas the ⌬perR sm mutant has a greatly reduced virulence potential.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, this FA-resistant mutant in S. enterica serovar Typhimurium shares with FA-resistant SCV mutants in S. aureus an auxotrophy in the heme biosynthesis pathway. It was earlier shown that mutations that directly affect heme biosynthesis, hemL in S. enterica serovar Typhimurium (16) or hemB in E. coli (49), result in SCVs that cause persistent and recurrent infections. In the case of fusA1, it is clear that the SCV-like phenotypes are indirect consequences of alterations in gene expression resulting from an aberrant EF-G-ribosome interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Additional features of SCVs often found are decreased respiration, increased resistance to aminoglycosides, reduced fermentation of sugars and an unstable phenotype (Proctor et al, 2006). Since SCVs can persist in host cells (Cano et al, 2003;Balwit et al, 1994) and might be less susceptible to antibiotics (Chuard et al, 1997) they are often associated with persistent or recurrent infections of the bone marrow, joints, soft skin, endocardium and the respiratory tract (Proctor et al, 2006). Supplementation with specific compounds such as menadione, haemin or thiamine can cause reversal of the SCV phenotype to the parental phenotype (electron-transport-defective SCVs) (Proctor et al, 2006).…”
Section: Introductionmentioning
confidence: 99%